LEGAL VOCABULARY OF ARABIC-SPEAKING ‘ADAT MONUMENTS IN 14TH-20TH CENTURY DAGESTAN (SOME RESULTS OF THE STUDY OF ISLAMIC DISCOURSES) - Bobrovnikov, Vladimir Olegovic (History, Archeology and Ethnography of the Caucasus, 2020)
The present article attempts at compiling a concise historical-legal dictionary of the legal custom or ‘adat practiced by Muslim highlanders in the North-East Caucasus from the 14th to the 20th centuries. It contains 108 terminological and phraseological items that the author gathered from documents as well as normative and narrative texts, including inscriptions. Characteristic for these terms and expressions is the inaccurate use of Arabic morphology and semantics. The author argues that these inaccuracies reflect the cultural translation of Dagestani historical realities into Arabic. The legal vocabulary of Dagestani ‘adat texts was created by Shari‘a judges as well as teachers and students of madrasas – that is, by persons with a rather good knowledge of classical Islamic legal literature – for members of their own rural communities and confederacies. ‘Adat agreements that had been concluded at meetings of the confederations were thereby translated into Arabic and written down in the margins of mosque Qur’ans and legal manuals; this process of translation and fixation in manuscript gave legitimacy to the agreements. The glossary offered here is meant to help readers of Arabophone sources from the North-East Caucasus. At the same time, the present publication points out controversies in the Islamic discourse that centered on issues of Dagestani ‘adat. The latter is understood here as a changing legal custom operating in the frameworks of Islamic law and then of the Russian imperial and early Soviet legal systems. Over the past twenty years, historians have analyzed the discourse of Dagestani scholars such as Muhammad of Kudutl, Dawud of Usisha and Murtada-‘Ali of Urada who in the seventeenth to nineteenth centuries took part in the Shari‘a movement against non-Islamic local customs. The present article draws attention to the circumstance that in judicial practice, these Shari‘a-minded scholars had to refer to various ‘adat norms and procedures reflecting the early modern society they lived in. At the same time, they contributed to gradual Islamization of legal custom. This process is reflected in the changing meanings of the terms as presented in this paper.